Remoção de cromo (VI) de soluções aquosas utilizando o compósito magnético calcinado hidrotalcita-óxido de ferro: estudo cinético e de equilíbrio termodinâmico Removal of chromium (VI) from aqueous solutions using the calcined magnetic composite hydrotalcite-iron oxide: kinetic and thermodynamic equilibrium studies - Thiago Vinícius Toledo; Carlos Roberto Bellato; Kenia Dias Pessoa; Maurício Paulo Ferreira Fontes (Química Nova, 2013)
In this work, hydrotalcite, a layered double hydroxide, had its ion exchange properties combined with the magnetic properties of iron oxide to produce a magnetic adsorbent, HT-Fe 500. These magnetic composites can be used as adsorbents for anionic contaminants in water and subsequently removed from the medium by a simple magnetic process. Removal of chromium (VI) from aqueous solutions using HT-Fe 500 was achieved using batch adsorption experiments. The adsorption capacity, calculated with the Langmuir-Freundlich model showed to be dependent on temperature, reaching values of 25.93 and 48.31 mg g-1, respectively, for temperatures of 25 and 30 ºC.